Psychological Dynamics in the Creative Process of Copywriters in the making of Advertisements - Wungu, Klaudia Mustika; Matulessy, Andik; Suryanto, S (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2019)
The purpose of this study is to describe: (1) the creative process of the copywriter in making advertisements, (2) the factors that hinder the creative process in making advertisements, (3) the factors that support the creative process. This study is based on Guilford’s theory which divides human thought processes into two types: divergent and convergent. This study uses a qualitative approach through observation and interviews. The subjects of this study were 3 media workers who worked as ad copywriters, aged between 25-40 years and were male & female. The results of this study indicate the copywriter as a creative person. The creative process that occurs when making advertisements in the form of briefings, brainstorming, and execution.